Prevalence of asthma symptoms among adolescents in Brazil: National Adolescent School-based Health Survey (PeNSE 2012) - Maurício Lima Barreto; Rita de Cássia Ribeiro-Silva; Deborah Carvalho Malta; Maryane Oliveira-Campos; Marco Antonio Andreazzi; Alvaro Augusto Cruz (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
OBJECTIVE: This study aims to describe the prevalence rates of asthma symptoms in Brazil, its Regions and State capitals, according to data from the National Adolescent School-based Health Survey, 2012. Furthermore, it aims to compare the prevalence of asthma in the capitals evaluated by PeNSE 2012 with previous results of the International Study of Asthma and Allergies in Childhood (ISAAC). METHODS: Cross sectional study of 9th grade students at public and private schools of all Brazilian states and the Federal District (Brasília). A self reported questionnaire containing items from the ISAAC was applied in order to identify the presence of asthma symptoms. RESULTS: The results of PeNSE indicate a high prevalence of asthma symptoms (23.2%) and of reports of a previous medical diagnosis of asthma (12.4%). Of the five state capitals in which the PeNSE results were compared to the ISAAC, São Paulo, Curitiba and Porto Alegre presented an increase in the prevalence of asthma symptoms. In Salvador, there was a reduction. CONCLUSION: Brazil is among the countries with the highest prevalence of asthma in the world, and the prevalence is still growing.